Image classification of coral reef species using wide residual network - Caneda, Ma. Abbygaile Joyce; Santos, Marko Jose
Monitoring and identifying coral reefs is tedious in its nature it requires marine experts to dive down the reefs and inspect corals manually. Moreover, the data gathered will still be analyzed by them. With the decline of the overall condition of corals in the country, it is in our best interest to lessen the workload of marine scientists.